Authoring diagrams that adapt to their viewing context. (June 2018) - McCormack, Cameron; Marriott, Kim; Meyer, Bernd
Abstract: The Web and digital media require documents whose appearance and content adapt to the viewing context and to user interaction. While most previous research has focussed on adaptation for textual and multimedia content, this is also true for diagrammatic content. We (a) identify the reasons for adaptation and the different kinds of adaptation that make sense for diagrams; (b) present an aspect-oriented model for diagram adaptation that separates adaptation into different orthogonal components; (c) describe a diagram authoring tool based on this model; and (d) present the results of a user evaluation of the tool. Our model uses layout "configurations" to model significantly different layout alternatives and geometric constraints to perform minor layout adjustment. The author can also specify alternate representations for an object, alternate styles and alternate textual content. The resulting space of different versions of the diagram is the cross product of these different alternatives. At display time the version is selected from this cross product and constructed automatically, taking into account the author specified preference order on the alternatives, current viewing environment, and user interaction. Abstract : Highlights: Analysis of reasons for adaptive presentation of diagrams. Classification of different kinds of adaptive presentation. Aspect-based model that overcomes combinatorial explosion of different versions. First tool for authoring diagrams that adapt their presentation. Conduct user evaluation of model and tool.